The Concept Time Value of Money from the Point of View of Islamic and Conventional Finance - Apriantoro, Muhamad Subhi; Mellinia, Rashifahunnisa'; Rosyadhi, Rozi Irfan (Institut Agama Islam Negeri Kendari, 2023)
The time value of money is the basic concept of elements and basic concepts of investment that are part of conventional financial theory. The value of everything now will be more significant in the future. This consideration system is not ruled out by Islamic finance because it covers the price of a commodity on every contract sale that must be paid in the future, and it is not forbidden to increase the price given. However, the time value of money in Islamic finance is different from conventional finance. In this discussion, describe the concepts of the time value of money from the point of view of Islamic and conventional finance, both theoretically and practically.